Digital Multimodality for Secondary School English Learning: Development and Evaluation of a Website-Based Instructional Platform - Iwan Fauzi; Orbit Thomas; Dina Mardiana (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study developed and evaluated a Digital Multimodality-Based Website (DMW) for teaching English language skills at the secondary school level. Grounded in social semiotic multimodality and the multiliteracies perspective, the study employed a Research and Development design using the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Data were collected from five certified English teachers, two expert validators, and 45 students of a state secondary school (SMA Negeri) through needs analysis questionnaires, expert validation forms, and user satisfaction surveys. The needs analysis showed strong teacher demand for an integrated, accessible, and culturally contextualized digital platform that combines reading, writing, listening, and speaking. Validation by ICT and English Language Teaching (ELT) experts showed that the DMW achieved high feasibility scores of 87.5% and 92.5%, indicating strong technical usability and pedagogical appropriateness. The product trial further showed positive student responses across usefulness (3.30), ease of use (3.35), ease of learning (3.35), and satisfaction (3.36). These findings indicate that the DMW was relevant to classroom needs, feasible to implement, and well-received by users. The study contributes a context-sensitive model for multimodal English learning that integrates digital literacy, local cultural content, and four-skill language instruction within a single platform.